Risk Factor Analysis and Molecular Epidemiological Investigation of Carbapenem-Resistant Enterobacteriaceae (CRE) Infection in Patients with Acute Pancreatitis - Yang F; Liu F; Zhao X; Chen Q (Infection and Drug Resistance)
Fangfang Yang,1 Fang Liu,2 Xiaoji Zhao,1 Qian Chen2 1Department of Clinical Laboratory, The Third Hospital of Mianyang, Sichuan Mental Health Center, Mianyang, People’s Republic of China; 2Department of Clinical Laboratory, Chongqing Red Cross Hospital (Jiangbei District People’s Hospital), Chongqing, People’s Republic of ChinaCorrespondence: Qian Chen, Chongqing Red Cross Hospital (Jiangbei District People’s Hospital), Chongqing, 400000, People’s Republic of China, Email qianchenfafafa@163.comObjective: Patients with acute pancreatitis (AP) complicated by carbapenem-resistant Enterobacteriaceae (CRE) infection often have a higher mortality rate. However, little investigation on the risk factor analysis has been published for the AP complicated by CRE. Therefore, this study conducted a retrospective analysis of the clinical characteristics, risk factors, and molecular epidemiological features associated with CRE infection in patients with AP.Methods: A total of 240 patients with AP were admitted to our hospital from 2011 to 2021 as the research objects, and were divided into a CRE group of 60 cases and a non-CRE group of 180 cases based on whether they were co-infected with CRE or not. Furthermore, both univariate analysis and multivariate analysis were used to analyze the risk factors of AP co-infection with CRE. In the CRE group, polymerase chain reaction (PCR) and agarose gel electrophoresis (AGE) were used to detect the expression of five common carbapenemase genes including blaKPC, blaIMP, blaVIM, blaNDM, and blaOXA-48.Results: The pathogenic bacteria in the CRE group are composed of Klebsiella pneumonia at 35.00%, Escherichia coli at 33.33%, Enterobacter cloacae at 25.00%, and Citrobacter freundii at 6.67%. Multivariate analysis showed that APACHE-II scores (OR=1.22), history of abdominal surgery (OR=81.82), and ERCP (OR=3.66) were independent risk factors for AP co-infection with CRE (P< 0.05). About half (18/40) of the CRE carried carbapenemase genes. blaKPC was the major carbapenemase gene.Conclusion: There are many risk factors for AP co-infection with CRE, which can occur in patients with high APACHE-II scores, experienced ERCP, and a history of abdominal surgery.Keywords: acute pancreatitis, carbapenem-resistant Enterobacteriaceae (CRE), infection, risk factors